Access to livelihood capitals and propensity for entrepreneurship amongst rice farmers in Ghana - Mumuni, Eliasu; Oladele, Oladimeji Idowu (BioMed Central, 2016)
Background: This paper examines rice farmers’ access to livelihood capitals (natural, financial, physical, social and human) and the relationship and propensity for entrepreneurship capacities amongst rice farmers in the northern and Ashanti regions of Ghana. A simple random and purposive sampling method was used to select a sample size of 301 rice farmers in the two regions. A structured questionnaire was used in conducting the study. The data was analysed with IBM SPSS version 21 using frequencies, percentages, means and standard deviation. Wilcoxon sign rank test, paired t test and Pearson correlation coefficient were also used for the analysis on the access to livelihoods, significance and relationship to entrepreneurial activities of the farmers. Results: Farmers’ access to natural capitals was stronger. Similarly, the Wilcoxon sign rank test and test statistics for the physical capital also revealed a significant difference in the farmers’ physical capitals with all the measured variables including irrigation infrastructure (z = −5.581; p = 0.000), processing facilities (z = −5.904; p = 0.000), and market access (z = −6.171; p = 0.000), after been exposed to the technology interventions. The test statistics shows significant difference in all the measured variables with the p value (p > 0.05) for the human capitals of the farmers. It also showed that farmers’ credit from family and friends, access to bank loans and loans from farmer groups all increased from 47 to 52 %; 26 to 37 % and 28 to 78 %, respectively. Generally farmers’ access to all the five livelihood capitals was significant and higher. On the access to livelihood capitals and its entrepreneurial abilities, natural capitals before (t = 1.789, p = 0.074), natural livelihood after (t = 1.664, p = 0.096), social capital after (t = 1.838, p = 0.066), and physical capital before (t = 2.87, p = 0.004) showed a significantly positive relationship with their entrepreneurial capacities. Conclusions: The study revealed that farmers’ access to stronger livelihood capitals improves on their internal locus of control, improves their farming management abilities and ultimately boosts their agricultural entrepreneurial capabilities. The study recommends that farmers should leverage on their human capitals (farming skills taught them) to improving on all other livelihood capitals for better business sense and culture and entrepreneurial skills.
DOI 10.1186/s40066-015-0049-x
Keywords: Livelihood capitals; Farmers; Rice; Entrepreneurship; Agriculture; Ghana